AUTHORITY AND PARTICIPATION IN ORGANIZATION THOUGHT - فخري فيصل (Dirasat in Economics and Business, 1976)
This study deals with the concepts of authority and power and their relationship to each other. It surveys as well the development of the concept of authority within consecutive theories. It also reviews the effects of this development towards arriving at a method by which the relationship between employee and management can be organized in a way insuring the well-being of the employee while the objectives of the organization. The article also discusses the concepts and developments at the level of organization without failing to pinpoint the importance of these concepts at various levels; personal, group, small society, large society and international.